A Project study on the systems and procedures of the National Power Corporation - Dans, Benjamin L.; Macatangay, Leah A.; Suarez, Kristen B.; Tanjuatco, Ferdinand P.; Tuason, Michael L.; Corpus, Gina B.; Dag, Benito C.; Eltanal, Eva Marie C.; Espina, Jesus S., Jr; Jaspe, Nilo B.; Montesa, Mary Margaret Q. (College of Engineering, 1982)
In a large and complex corpora ion such as the NPC, it is very important to have orderly work processes and flows. This would ensure a minimum, if any, of duplicated function or problem areas in terms of organizational structure and links. Systems and Procedures (S&P) is a term used in the management of systems to describe: 1) how things must be done; 2) ways and means to accomplish them; and 3) methodology of the work processes used. Thus, what many would ignore as an inherent component of any business, is actually a very complicated field of endeavor that should be studied, improved, and evaluated in an ongoing process. Because of the size of NPC, it would be difficult to point out in great detail the entire network of S&P being used in each division. This study, therefore, focused on tackling the S&P of NPC as a whole, by finding the links and operational flows on departmental level. Using the methodology earlier described, the study progressed through comprehensive data-gathering and interviews. It was through interviews that the research group was able to become more acquainted with the corporation and see the many fine points in the contribution of each department in terms of their functions. With the data gathered, as well as in research in other sources of information, as analysis of the major operational flows was made. This became the basis of the sections to follow. The design alternatives of the systems and procedures system came in the pre-feasibility analysis. Here, too, a great deal of detail was included so as to provide for possible solutions to the areas of concern earlier described in the data analysis. From here, the feasibility studies scrutinized and re-scrutinized each alternative in terms of its market, technical aspect, financial aspect. This led to the design selection and eventual refinement. In the course of this study, there has been the unifying goal of finding ways to improve the S&P system of NPC and make a "visible change" in the efficiency and effectivity of the opera ions of this government entity. This would, in the final analysis, make NPC a system serving in a better manner a larger system -- the Filipino people.